1989
DOI: 10.1002/ana.410250509
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and intermittent levodopa differentially affect basal ganglia function

Abstract: The effects of continuous and intermittent levodopa treatment on behavioral and biochemical indexes of basal ganglia function were compared in rats with unilateral 6-hydroxydopamine lesions of the nigrostriatal dopamine pathway. Animals treated for 30 days with intermittent levodopa exhibited behavioral sensitization manifested by an enhanced rotational response to apomorphine; the rotational response of rats treated with an equivalent dose of levodopa by continuous infusion did not differ from that of saline-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(33 citation statements)
references
References 42 publications
(3 reference statements)
1
32
0
Order By: Relevance
“…It is evident that a thorough understanding of this issue will require additional data regarding the effects of L-DOPA under conditions of impaired striatal function. It has been suggested that differences may exist in response to L-DOPA as a function of mode of L-DOPA infusion (Bennett etal., 1989;Chase et al, 1989;Gauthier and Amyot, 1992;Mouradian et al, 1990); differences which cannot be necessarily attributable to the dose of L-DOPA Juncos et al, 1989). Therefore, in the present report we included a comparison between a brief 10-minute versus continuous 60-minute infusion of L-DOPA.…”
Section: Discussionmentioning
confidence: 91%
“…It is evident that a thorough understanding of this issue will require additional data regarding the effects of L-DOPA under conditions of impaired striatal function. It has been suggested that differences may exist in response to L-DOPA as a function of mode of L-DOPA infusion (Bennett etal., 1989;Chase et al, 1989;Gauthier and Amyot, 1992;Mouradian et al, 1990); differences which cannot be necessarily attributable to the dose of L-DOPA Juncos et al, 1989). Therefore, in the present report we included a comparison between a brief 10-minute versus continuous 60-minute infusion of L-DOPA.…”
Section: Discussionmentioning
confidence: 91%
“…Levodopa induces shortening of the motor response (wearing-off) in parkinsonian rodents when it is given intermittently but not when it is administered continuously. 295 Short-acting dopaminergic agents such as levodopa are more prone to induce dyskinesia in MPTP-treated monkeys than are long-acting dopaminergic agents such as bromocriptine and ropinirole. 296,297 Of particular importance is the observation that the same short-acting dopaminergic agent that induces dyskinesia when administered in a pulsatile manner does not induce dyskinesia when administered continuously.…”
Section: 242mentioning
confidence: 99%
“…The up-regulation in striatal D2 dopamine receptor density observed in 6-OHDA lesioned rats is reduced, or further enhanced following chronic intermittent levodopa administration (Gnaalingham & Robertson, 1994;Rouillard et al, 1987). Chronic intermittent levodopa treatment has also been shown to reverse the DI-receptor upregulation observed in the denervated striatum (Juncos et al, 1989). However, in some studies, [3H]-SCH23390 binding in the striatum and nucleus accumbens was unaffected by levodopa treatments (Rioux et al, 1993).…”
Section: Introductionmentioning
confidence: 99%